Evaluation of real-time polymerase chain reaction for detection of Strongyloides stercoralis in immunocompromised patients in North India - Dr Abhishek Mewara; Ms. Nikita Sharma; Dr Gaurav Prakash; Dr Vignesh Pandiarajan; Dr Sahajal Dhooria; Dr Varun Dhir; Dr Surjit Singh; Dr Ritesh Agarwal (International Journal of Infectious Diseases)
Introduction: The diagnosis of Strongyloides stercoralis remains challenging as the commonly used stool microscopy has poor sensitivity, culture is cumbersome to perform, and serology is not always indicative of current infection. In this study, we evaluated real-time polymerase chain reaction (RT-PCR) for detection of Strongyloides stercoralis in immunocompromised patients in comparison with serology, microscopy and culture Methods. Methods & Materials: A total of 498 patients with immunosuppressive conditions and/or on steroids/cytotoxic medications from various specialties of our tertiary care hospital in North India were enrolled from December 2020 to March 2022 for collection of paired stool and serum samples on two occasions. Paired stool and serum samples from 135 controls were also obtained from apparently healthy subjects. The stool samples were subjected to microscopy, Agar plate, Baermann's funnel and Harada Mori culture techniques, and in-house 18S rRNA gene RT-PCR, and serum were subjected to anti-Strongyloides IgG antibody ELISA by a commercial kit. The diagnostic efficacy was evaluated by using a composite reference standard, i.e., positive by at least one of the tests. Results: Of the 498 paired initial screening samples, 67 (13.5%) were positive by serology (14 of which were positive by RT-PCR), with a sensitivity and specificity of 79.8% (95% CI 69.9-86.9) and 95.5% (95% CI 93.3-96.9) respectively. Similarly, 31 (6.2%) were positive by RT-PCR (14 of which were positive by ELISA), with a sensitivity and specificity of 36.9% (95% CI 27.4-47.6) and 99.8% (95% CI 98.9-99.9) respectively; the limit of detection of RT-PCR was 81.6 ag/µL. The microscopy and helminth culture showed poor sensitivity as only 8 (1.61%) were positive by these Methods. On including the second sampling, 98 (19.68%) out of 498 patients were found positive by either of the tests on either of the two sampling occasions. Of these 98 patients, there were 76 (15.26%) positive by serology, 36 (7.23%) by RT-PCR, and 8 (1.61%) by microscopy and culture Methods. The infected patients were from various clinical specialties, belonged to both rural and urban localities, and were distributed across 07 states of India. Discussion: A high prevalence of S. stercoralis infection was observed in immunosuppressed patients from different clinical specialties in North India using serological and molecular methods, while stool microscopy and helminth culture methods missed a large proportion of the infections. The infected individuals were from both urban and rural backgrounds and from widely distributed geographical locations in North India. Conclusion: S. stercoralis infection is widely endemic in North India and is a diagnostic challenge. For detection of S. stercoralis infections, a judicious selection of more than one laboratory assays is recommended based on the specific need, such as community mapping, patient screening or diagnosis, to ensure effective control of the disease.